2015
DOI: 10.1002/eat.22473
|View full text |Cite
|
Sign up to set email alerts
|

Attachment and mentalization and their association with child and adolescent eating pathology: A systematic review

Abstract: In keeping with the adult literature, cross-sectional studies of children and adolescents consistently report associations with eating pathology. There is some evidence from prospective studies that insecure attachment may be a risk factor for the development of eating pathology in adolescence. The literature on mentalization and eating pathology suggests that adolescents with anorexia nervosa may have difficulties in recognizing emotions. Further research using clinical samples and well-validated measures of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
87
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(109 citation statements)
references
References 117 publications
(212 reference statements)
12
87
0
3
Order By: Relevance
“…Recently, two different studies using dynamic causal modeling identified a relationship between left parietal regions and medial prefrontal cortex important for self-specific processing in healthy adults (Davey et al, 2016; Sui et al, 2013); disruption of this neurocircuitry may be important in the pathology of AN. In a systematic review, Jewell (Jewell et al, 2016) reported that a consistent relationship between eating pathology and mentalization difficulties has been observed in adolescents with eating disorders; here we propose neural regions that may mediate these problems.…”
Section: Discussionsupporting
confidence: 54%
“…Recently, two different studies using dynamic causal modeling identified a relationship between left parietal regions and medial prefrontal cortex important for self-specific processing in healthy adults (Davey et al, 2016; Sui et al, 2013); disruption of this neurocircuitry may be important in the pathology of AN. In a systematic review, Jewell (Jewell et al, 2016) reported that a consistent relationship between eating pathology and mentalization difficulties has been observed in adolescents with eating disorders; here we propose neural regions that may mediate these problems.…”
Section: Discussionsupporting
confidence: 54%
“…Early attachment experiences increase the risk of eating disorders [76•, 77] and obesity [78]. Furthermore, adolescents [79,80] and adults [81,82] with AN have insecure patterns of attachment. A recent meta-analysis concluded that this effect was large (Cohen's d = 1.…”
Section: Early Adversity and Eating Behaviourmentioning
confidence: 99%
“…And also in eating disorders attachment was found to be a predictor of risk. (Szalai and Czegledi 2015); (Jewell et al 2016) However, there remains a paucity of research on the relationship between attachment and defenses. The few studies that have been conducted indicate an association between attachment styles and specific defense mechanisms.…”
Section: Introductionmentioning
confidence: 99%